A new species of Pericallis (Senecioneae, Asteraceae) endemic to Porto Santo (Madeira, Portugal) - Jones, Katy Elizabeth (2022)
A new species, Pericallis menezesii, is described from the island of Porto Santo in the Madeiran archipelago. Morphological comparisons are made with its sister taxon, P. aurita which is now considered to be endemic to the island of Madeira.